Angling for Sharks, Not Pilot Fish: Deep Corruption, Venal Corruption, and Public Values Failure. Issue 1 (27th September 2017) - Bozeman, Barry; Molina, Angel Luis; Kaufmann, Wesley
Abstract: The existing literature in public administration and related disciplines tends to view government corruption in terms of legal transgression, specific acts by public officials in violation of public law. The present authors contend that a particularly worrisome form of corruption, one generally overlooked in the literature, is deep corruption, acts by public officials thwarting public values but acts not necessarily countermanded by public laws. Examples of deep corruption include pervasive use of excessive and targeted (but possibly legal) deadly force and measures to abridge voting rights, such as erecting increasingly stringent (legal) barriers to voting, barriers chosen because they differentially affect voting groups less favored by the public officials advocating the barriers. Generally, deep corruption has greater potential for social damage than do specific incidents involving bribes and kickbacks. Drawing on public values theory, the authors argue that the concept public values failure is a useful starting point for identifying and possibly explaining instances of deep corruption.